2018
DOI: 10.12968/hmed.2018.79.10.578
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and interpreting funnel plots for the clinician

Abstract: Funnel plots are an increasingly common graphical tool which are widely used in the literature. They were first introduced by Light and Pillemer in 1984 . In scientific literature, funnel plots are used to identify the probability of bias in meta-analyses and compare institutional performance. The ability to identify variation is better with graphical than tabular display. In addition, the way data are presented can directly influence the interpretation of results. This was demonstrated by Marshall et al (200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…The pooled prevalence identified in this study was estimated from studies with moderate to high quality. No discovered publication bias distorted the result of the estimated prevalence of CKD by the funnel plot and Egger's test [59].…”
Section: Plos Onementioning
confidence: 99%
“…The pooled prevalence identified in this study was estimated from studies with moderate to high quality. No discovered publication bias distorted the result of the estimated prevalence of CKD by the funnel plot and Egger's test [59].…”
Section: Plos Onementioning
confidence: 99%
“…Among the reasons, it was observed a variety of healthcare providers as participants in the selected primary studies, as shown in Chart 1. Thus, in order to reduce heterogeneity, a subgroup analysis was performed (29) . Firstly, subgroups were generated according to the setting of activity of the study participants: emergency and surgery room.…”
Section: Resultsmentioning
confidence: 99%
“…Another important analysis was the creation of subgroups with studies that assessed more than one supraglottic device compared to orotracheal tube, thus conferring a reproductive characteristic of the methodology. The methodological variation of each study is known to have a direct impact on the heterogeneity of data for meta-analyses (29,33) . Low heterogeneity (0 < I2 < 12%) and statistically significant results were obtained in the methodological reproduction subgroups, corroborating the previous analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A heterogeneity score > 60% was used to investigate the variability of the reported results. Publication bias in the outcomes of included studies was assessed by the construction of funnel plots [12] . The pairwise assessment of the study outcomes guided the analysis of their clinical correlation with pre-AF/NOAF versus sinus rhythm.…”
Section: Methodsmentioning
confidence: 99%